Retrieval of optical and microphysical properties of transported Saharan dust over Athens and Granada based on multi-wavelength Raman lidar measurements: Study of the mixing processes. (1st October 2019) - Soupiona, O.; Samaras, S.; Ortiz-Amezcua, P.; Böckmann, C.; Papayannis, A.; Moreira, G.A.; Benavent-Oltra, J.A.; Guerrero-Rascado, J.L.; Bedoya-Velásquez, A.E.; Olmo, F.J.; Román, R.; Kokkalis, P.; et al.
Abstract: In this paper we extract the aerosol microphysical properties for a collection of mineral dust cases measured by multi-wavelength depolarization Raman lidar systems located at the National Technical University of Athens (NTUA, Athens, Greece) and the Andalusian Institute for Earth System Research (IISTA-CEAMA, Granada, Spain). The lidar-based retrievals were carried out with the Spheroidal Inversion eXperiments software tool (SphInX) developed at the University of Potsdam (Germany). The software uses regularized inversion of a two-dimensional enhancement of the Mie model based on the spheroid-particle approximation with the aspect ratio determining the particle shape. The selection of the cases was based on the transport time from the source regions to the measuring sites. The aerosol optical depth as measured by AERONET ranged from 0.27 to 0.54 (at 500 nm) depending on the intensity of each event. Our analysis showed the hourly mean particle linear depolarization ratio and particle lidar ratio values at 532 nm ranging from 11 to 34% and from 42 to 79 sr respectively, depending on the mixing status, the corresponding air mass pathways and their transport time. Cases with shorter transport time showed good agreement in terms of the optical and SphInX-retrieved microphysical properties between Athens and Granada providing a complex refractive index value equal to 1.4 + 0.004i. On the other hand, the results for cases with higher transport time deviated from the aforementioned ones as well as from each other, providing, in particular, an imaginary part of the refractive index ranging from 0.002 to 0.005. Reconstructions of two-dimensional shape-size distributions for each selected layer showed that the dominant effective particle shape was prolate with diverse spherical contributions. The retrieved volume concentrations reflect overall the intensity of the episodes. Highlights: Inversion of a two-dimensional enhancement of the Mie model based on the spheroid-particle approximation. Reconstructions of two-dimensional shape-size distributions for selected layers. Focus on short range (pure) to long range (mixture) dust processes. Mean δaer and LR values at 532 nm range from 11 to 34% and from 42 to 79 sr respectively, depending on the mixing state. AOD as measured by AERONET ranged from 0.27 to 0.54 (at 500 nm) depending on the intensity of each event.